Relationship between internet addiction and mental health in adolescents - Yousef Veisani; Zahra Jalilian; Fathola Mohamadian (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Internet addiction (IA) currently is the major public health concern, especially in adolescents, although the results of previous reports are not generally uniform. This study was conducted to determine IA in adolescents and to examine the correlation of IA with mental health in adolescents. METHODS: This cross-sectional study was conducted in 2019 in Ilam city. In this study, 362 persons were included using stratified cluster sampling; clusters were geographical area and schools. The valid questionnaires including Internet Addiction Test and 28-item General Health Questionnaire (GHQ-28) were used to interview. The correlation statistical technique was used to determine the association between the two variables. The significance level was considered <0.05. RESULTS: The mean ± standard deviation age of the responders was 16.40 ± 2.47 years; the total score of IA and mental health was 43.02 ± 16.50 and 19.27 ± 9.72, respectively. We found that 5.5% of the adolescents had a severe level of IA. The lack of control with anxiety, neglect work and social dysfunction, and neglect social life and severe depression in internet users were found to be statistically significant: r (365) = 0.151, P < 0.033; r (365) = 0.126, P < 0.021; and r (365) = 0.125, P < 0.033, two-tailed, respectively. CONCLUSION: According to the results, the excessive use of internet, lack of control, and neglect social life are significantly correlated with mental health in adolescents; these results could be contribute to improve the theoretical models for IA in adolescents.